Politicals for the social inclusion through ICT - Iolanda GARCÍA GONZÁLEZ (Ediciones Universidad de Salamanca, 2016)
This article deals with policies and programmes addressed to young people at a social risk, which incorporate uses of information and communication technologies (ICT). On the base of the description of some social exclusion emerging forms in the information society, we will analyse the kind of responses provided in terms of public policies. Furthermore, we will try to demonstrate the added value that ICT confer to this kind of programmes, specifically addressed to young population.